Exploring the Insider–Outsider Status of Postgraduate Students in Leading Lesson Study - James Calleja; Laura Formosa (Trends in Higher Education)
Lesson study, a collaborative teacher professional development approach, has gained popularity internationally and leading the process with teachers plays a key role in making it sustainable in schools. This paper, which draws on a postgraduate university course for prospective school leaders, examines the dynamic roles in leading lesson study. Drawing on the literature on lesson study and leadership, we analyse how postgraduate students lead lesson study while navigating their status as an insider–outsider. Using a theoretical lens informed by the insider–outsider researcher debate, we propose a classification framework to understand lesson study leaders’ statuses. Presenting two case studies, we explore the strategies for the selection of LS participants, communication, and trust-building, as well as the leaders’ dilemmas and learning opportunities. Drawing on the findings, we highlight the central role of reflective practice in leading lesson study and offer insights for practitioners. This study sheds light on the nuanced dynamics of leading lesson study and its implications for the preparation of prospective leaders.